Nutrition and response to covid-19 in fishermen from huanchaco (peru) - Bocanegra García, Carlos A.; León Risco, Anthony Omar (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
There are works on immunological resistance in animals and humans on the defensive capacity against pathogens such as bacteria and viruses. Foods are not strictly medicines, but they contain nutrients such as proteins, vitamins, and minerals, which allow a good state of health and constitute a response to various infectious diseases. The study focuses on the eating habits of Huanchaco fishermen who feed mainly on fish. The objective was to determine if fish-based nutrition would be related to the immune response to COVID-19. The results showed a mortality of 6.66%.